The Role of Financial Literacy and Beliefs in Investment Decision Making - Mediaty; Habbe, Abdul Hamid; PRATIWI, RIZKY INMAS; Batara, Angela; Irfan, Lidya Pratiwi; Azizah, Nur (Hasanuddin Economics and Business Review, 2025)
Distinct from prior work that emphasises either financial literacy alone or broad student populations, this paper jointly examines financial literacy and financial self-efficacy as drivers of investment decision-making among accounting students a cohort of prospective finance professionals within Indonesia’s evolving OJK-led financial inclusion and investor-education ecosystem. A cross-sectional survey of 50 active undergraduate and postgraduate accounting students from Hasanuddin University and Universitas Muslim Indonesia in Makassar (tertiary education sector; accounting programmes) was analysed using PLS-SEM (SmartPLS 3.3.9, bootstrapping). Results indicate a positive, significant effect of financial literacy on investment decisions (β = 0.741, p = 0.001), while financial self-efficacy is negative and non-significant (β = −0.113, p = 0.563), with the model explaining 41.7% of variance (R² = 0.417). The evidence suggests that knowledge-based competence, rather than confidence alone, underpins higher-quality investment choices in this context. A policy-ready implication follows: curriculum-embedded financial education with supervised practice (campus investment clinics co-run with IDX–OJK partners and broker-dealers) is likely to outperform confidence-building campaigns delivered in isolation. By offering Indonesia-specific, management- and policy-relevant evidence on decision quality in an emerging-market setting, the manuscript contributes to debates at the intersection of behavioural finance, education, and economic management germane to HEBR’s readership.